PENGARUH MANAJEMEN LABA DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN MEKANISME CORPORATE GOVERNANCE - Galuh Setiawati; Windy Freshillya; Soexma Ayu Mustika Ningrum (CV. Denasya Smart Publisher, 2024)
This study aims to determine the effect of earnings management and financial performance on firm value with the Corporate Governance mechanism in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The type of research used is quantitative with sampling using purposive sampling of 7 companies from 56 populations. The analysis technique uses simple regression analysis, classical assumption test and MRA test or Moderated Regression Analysis and the data is processed using SPSS 26. The results showed that partially showed that none of the independent variables (Earnings Management, ROA, ROE, and CR) had a significant effect on the dependent variable Company Value / PBV because the t value of all variables < t table (2.119). However, simultaneously the independent variables of earnings management and ROA together have a significant effect on the dependent variable (Firm Value) in a simple regression model. Meanwhile, based on the moderation t test and moderation f test, the independent variables, namely earnings management, ROA, ROE, CR with moderation variables, namely managerial ownership, institutional ownership, independent board of commissioners, have no significant effect on firm value / PBV.